Livestock Policy Analysis Brief no. 9 . Fertiliser use in semi-arid West Africa: Profitability and supporting policy - Shapiro, Barry I.; Sanders, J.H. (International Livestock Research Institute, 1998)
An important debate is currently under way among researchers and policy makers about the relative merits of using organic versus inorganic fertilisers to improve soil fertility in semi-arid areas of sub-Saharan Africa. Environmentalists argue that use of inorganic fertiliser contributes to natural resource degradation and recommend use of organic fertilisers as a means of promoting sustainable agriculture. Opponents of this view maintain that a more rapid introduction of inorganic fertilisers is required in sub-Saharan Africa where current levels of use are extremely low, even when compared with other developing countries. This debate has important implications for agricultural intensification and sustainable development in the Sudanian and Sahelo-Sudanian agro-ecological zones of semi-arid West Africa. This paper assesses the profitability of using inorganic fertiliser and constraints posed on its use in the semi-arid farming systems of West Africa. It argues that under current conditions in these regions, organic and inorganic fertilisers are complements and not substitutes. The critical requirement for improving food production in these regions is to increase the use of inorganic fertiliser. Government policies need to support fertiliser importation and diffusion with conductive policies.